Współczesna rola państwa w finansowaniu budownictwa mieszkaniowego - Szelągowska, Anna (The Contemporary Role of Government in the Housing Construction's Financing, 2009)
The high level of the housing shortage in Poland results from the low government inputs on housing. The long-term higher financial support of the government could improve the revival of housing demand and create favourable conditions for meeting the basic housing needs. The role of government in financing social housing needs is connected with their increasing level. What is more, state support has a special importance in the age of world financial crisis which has a negative influence on the Polish housing market. Therefore, launching the new government housing programme stimulates both demand and supply side of housing market. As a result, it will improve the economic growth of Poland in the long term
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 332-338